General Theory and Local Action: Experiences from the Quality of Working Life Movement - Gustavsen, Bjørn (Nordic Journal of Working Life Studies, 2017)
Quality of Working Life was a researcher-driven social movement culminating in the early 1980s. Its 1981 conference had some 2000 participants from research, management, unions, and government from about 30 countries. Their unifying idea was that the kind of workplace organization demonstrated in the Industrial Democracy Experiments had an emancipatory potential for democracy, productivity, and health in the workplace and beyond. A key question remained, however: how could this transformation take place on a large scale in society? There were different attempts within the movement at combining the general frameworks required to maintain societal significance and impact on the one hand, at the same time as creating relevant knowledge for the local context. After leaving the initial ambition of a universal theory, a turn toward purely local development work was again followed by a return to the general, not as the foundation of a general theory but as elements in a social movement.